Heparin-Induced Fever in Neurointensive Care Unit: A Rarity Yet a Possibility - Krishnakumar, Mathangi; Naik, Shweta S.; Ramesh, Venkatapura J.; Mouleeswaran, S (Journal of Neuroanaesthesiology and Critical Care, 2021)
Fever is considered a protective response having multitude of benefits in terms of enhancing resistance to infection, recruiting cytokines to the injured tissue, and promoting healing. In terms of an injured brain, this becomes a double-edged sword triggering an inflammatory cascade resulting in secondary brain injury. It is important to identify the etiology so that corrective measures can be taken. Here we report a case of persistent fever in a patient with Guillain-Barré syndrome, which was probably due to heparin. This is the first report of heparin-induced fever in a neurocritical care setting and third report overall.
Keywords: heparin; drug fever; hyperthermia; NICU; neurological disease